2012
DOI: 10.1002/hed.23172
|View full text |Cite
|
Sign up to set email alerts
|

Neck metastases in oropharyngeal cancer: Necessity and extent of bilateral treatment

Abstract: Bilateral neck disease in OPSCC is more common than once thought. Patients with OPSCC with cT4 or cN2a+ would benefit from bilateral neck treatment. Posttreatment high-risk features should guide treatment escalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In the study by Buckley et al, only those cases with an N stage of N1, N2a, and N2b were included . From Dziegielewski et al, only those cases with an N stage of N1 or N2a could be used …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study by Buckley et al, only those cases with an N stage of N1, N2a, and N2b were included . From Dziegielewski et al, only those cases with an N stage of N1 or N2a could be used …”
Section: Resultsmentioning
confidence: 99%
“…The survival data for most studies were excluded from this review because survival outcomes were often pooled with irrelevant data. Da Mosto et al and Dziegielewski et al reported a 5‐year disease‐free survival (DFS) of 58.3% and 87%, respectively, but these figures included some patients with initially clinically staged N0 neck disease . For both studies, regional recurrence for the clinically N‐positive neck with level V uninvolved was still able to be determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, successful treatment and better prognosis often depended on tumour staging, local extension, anatomical tumour site, histotype, lymph node involvement and locoregional disease control [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%